Healed plaque erosion as a cause of recurrent vasospastic angina: a case report. Issue 10 (4th September 2021) - Yamamoto, Tetsuya; Toshimitsu, Ishii; Ishida, Akihiko
Abstract: Background: Recurrent vasospastic angina sometimes occurs. Fresh thrombi have been known to arise without plaque rupture at coronary spasm sites due to blood flow stagnation and intimal erosion caused by vasospasms. The relationship between recurrence of vasospastic angina and thrombus formation remains unclear. Case summary: A 67-year-old man presented with sudden chest pain at rest. Electrocardiography and coronary angiography indicated vasospastic angina. His chest pain persisted despite the administration of benidipine, isosorbide mononitrate, nicorandil, and nifedipine. Coronary angiography performed one month after initial presentation showed stenosis refractory to isosorbide administration. Optical coherence tomography revealed a healed plaque, and a stent was deployed. The patient remained symptom-free at 1-year follow-up. Discussion: Prolonged coronary vasospasm with limited coronary blood flow could induce total occlusion of the coronary artery, and acute thrombus formation, which resulted in healed plaque erosion. When vasospastic angina cannot be controlled, rapidly progressive stenosis caused by healed plaque erosion could be its underlying cause and mechanism. This report indicates that antiplatelet therapy may be a preventive option for future recurrent vasospastic angina, especially in those caused by healed plaques.